2002
DOI: 10.1080/08958370290084908
|View full text |Cite
|
Sign up to set email alerts
|

SPORES OF Aspergillus versicolor ISOLATED FROM INDOOR AIR OF A MOISTURE-DAMAGED BUILDING PROVOKE ACUTE INFLAMMATION IN MOUSE LUNGS

Abstract: Microbial growth in moisture-damaged buildings has been associated with respiratory health effects, and the spores of the mycotoxin producing fungus Aspergillus versicolor are frequently present in the indoor air. To characterize the potential of these spores to cause harmful respiratory effects, mice were exposed via intratracheal instillation to a single dose of the spores of A. versicolor (1 x 10(5), 1 x 10(6), 5 x 10(6), 1 x 10(7), or 1 x 10(8) spores), isolated from the indoor air of a moisture-damaged bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…Aspergilli are primary colonizers and can be customized to a w values below 0.8, which allows them to succeed in damp indoor environments more likely than other moulds (22,39). Aspergillus versicolor is the most frequently reported fungal species in section Versicolores from damp indoor environments and its presence might be related to Sick Building Syndrome (17)(18)(19)(20). Recent publications based on the molecular identification of Aspergillus species (Versicolores) indicated that Aspergillus versicolor sensu stricto were not common in buildings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergilli are primary colonizers and can be customized to a w values below 0.8, which allows them to succeed in damp indoor environments more likely than other moulds (22,39). Aspergillus versicolor is the most frequently reported fungal species in section Versicolores from damp indoor environments and its presence might be related to Sick Building Syndrome (17)(18)(19)(20). Recent publications based on the molecular identification of Aspergillus species (Versicolores) indicated that Aspergillus versicolor sensu stricto were not common in buildings.…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus flavus and A. parasiticus from the Flavi section are important producers of the highly toxic and carcinogenic aflatoxin B1 and these species grow on almost all crops (16). Aspergillus versicolor is the most frequently reported Versicolores fungus from damp indoor environments and its presence might be related to Sick Building Syndrome (17)(18)(19)(20). Moreover, it represents a special threat for human health due to its very small spores and release of mycellium fragments (10) as well as ability to produce sterigmatocystin (21,22).…”
mentioning
confidence: 99%
“…versicolor is commonly found in unhealthy indoor environments and studies have shown that inhalation exposure to Asp. versicolor spores may cause acute inflammation and cytotoxic effects [27,28]. To this end we analyzed seven different Asp.…”
Section: Translation Inhibition For Aspergillus Versicolor Isolatesmentioning
confidence: 99%
“…Despite the lack of firm evidence concerning the effects of fungal exposures on immune responses emerging from this study, living in a moisture-damaged building and the presence of mold seem to increase the risk of respiratory symptoms, but rarely allergic sensitization, in childhood [9,39]. In addition, previous in vitro [40] and in vivo [41] studies imply that fungal components derived from moldy buildings have a real capacity to evoke severe health problems. However, further studies are needed to investigate the extent to which fungal exposures affect immune development and the health of newborns.…”
Section: Discussionmentioning
confidence: 96%